2018
DOI: 10.1093/asj/sjy060
|View full text |Cite
|
Sign up to set email alerts
|

Perioral Rejuvenation: A Prospective, Quantitative Dynamic Three-Dimensional Analysis of a Dual Modality Treatment

Abstract: Background The perioral region is the most dynamic anatomic area of the face and subject to complex and dramatic changes during aging. Successful treatment for perioral rejuvenation has yet to be identified, and prior studies have reported only subjective outcomes. Objectives The purpose of this study was to utilize our validated dynamic 3-dimensional imaging technology to determine whether conservative neuromodulation combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…A total of 625 papers were identified in the electronic database searches; 65 duplicate papers were excluded before citation screening and 510 papers were excluded during citation screening ( Figure 1 ). There were no relevant studies identified in the supplementary searches, and 40 of the remaining 50 papers were excluded during full-text review, leaving 10 studies (three observational studies [OSs] [ 21 , 22 , 23 ], five non-randomized controlled trials [ 24 , 25 , 26 , 27 , 28 ] and two studies reporting data from one randomized controlled trial [RCT] [ 29 , 30 ]) included in the SLR. In the included studies, sample size ranged from 10 to 383 patients, mean age was 32.8 to 55.9 years and percentage of female participants was 92.7% to 100% across six studies that reported gender.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 625 papers were identified in the electronic database searches; 65 duplicate papers were excluded before citation screening and 510 papers were excluded during citation screening ( Figure 1 ). There were no relevant studies identified in the supplementary searches, and 40 of the remaining 50 papers were excluded during full-text review, leaving 10 studies (three observational studies [OSs] [ 21 , 22 , 23 ], five non-randomized controlled trials [ 24 , 25 , 26 , 27 , 28 ] and two studies reporting data from one randomized controlled trial [RCT] [ 29 , 30 ]) included in the SLR. In the included studies, sample size ranged from 10 to 383 patients, mean age was 32.8 to 55.9 years and percentage of female participants was 92.7% to 100% across six studies that reported gender.…”
Section: Resultsmentioning
confidence: 99%
“…In the included studies, sample size ranged from 10 to 383 patients, mean age was 32.8 to 55.9 years and percentage of female participants was 92.7% to 100% across six studies that reported gender. Three studies were conducted in Brazil [ 22 , 29 , 30 ], two in Lebanon [ 24 , 26 ], two in the USA [ 21 , 27 ] and one each in South Korea [ 25 ], Taiwan [ 28 ] and Thailand [ 23 ]. Six of the studies looked at aboBoNT-A injections in various parts of the middle and lower regions of the face for the treatment of various conditions, including lower eyelid wrinkles, nasal wrinkles, platysmal bands at rest and at maximal contraction and marionette lines [ 23 , 24 , 26 , 27 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We introduced a new CML technique to reduce postoperative scarring and reported our results. A considerable amount of research has been performed on aging lips, and lip surgery has mainly been conducted as an ancillary procedure in facial rejuvenation [5]. A traditional facelift may improve jowl and marionette lines to a certain extent.…”
Section: Discussionmentioning
confidence: 99%